DETRIMENTAL IMPACT OF CRYOPRESERVATION ON BUFFALO BULL SPERM MOTILITY, VIABILITY AND MEMBRANE INTEGRITY DUE TO EFFLUX OF MEMBRANE CHOLESTEROL - SINGH, N; CHEEMA, RS; KUMAR, A; KAUR, M; DHALIWAL, GS (The Indian Journal of Animal Reproduction, 2016)
Thirty ejaculates from six buffalo bulls were used in the present study. Subsequent to cryopreservation, cholesterol content of buffalo bull sperms was reduced as compared to pre-freeze stage (p<0.05). From prefreeze to post-thaw stage, a marked decrease was recorded in sperm motility, viability and membrane integrity (p<0.05). It brief, the efflux of cholesterol from sperm membrane during cryopreservation might lead to decrease in sperm motility, viability and membrane integrity vis-à-vis decrease in fertility of frozen-thawed semen.